10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Background Encephalitozoon cuniculi is an obligate intracellular parasite belonging to the phylum Microsporidia, family Encephalitozoonidae. The parasite is distributed worldwide and infects a variety of mammals, with rabbits being the main host. Currently, the most reliable diagnostic method is serological testing, but various molecular techniques are also being used. Objective This study assesses the presence, genotypes and clinical signs of E. cuniculi infection in pet rabbits in Slovenia, using molecular and serological methods. Methods From January 2022 to 2024, urine samples from random pet rabbits (n = 247) were collected for polymerase chain reaction (PCR) testing and transmission electron microscopy (TEM) to search for the presence of E. cuniculi genetic material or spores. Results With the real-time PCR, E. cuniculi genetic material was detected in 37 of 247 (14.98%) rabbit urine samples. Serological testing revealed specific immunoglobulin M (IgM) and/or immunoglobulin G (IgG) antibodies in 91 of 133 rabbits (68.42%). A quarter of the serologically positive rabbits (25.27%) and almost half of the molecularly positive rabbits (43.24%) were clinically healthy and showed no signs of encephalitozoonosis. E. cuniculi genetic material in urine was mostly discovered in rabbits with signs of urinary tract disorders (27.03%) or neurological clinical signs (21.62%). Genotype I of E. cuniculi was detected in all rabbits. Despite the detection of the pathogens' DNA, no E. cuniculi spores were observed by TEM. Conclusion E. cuniculi infection is common among pet rabbits in Slovenia, with a high seroprevalence and detectable urinary shedding of parasite DNA. The presence of clinically healthy but infected rabbits indicates that subclinical infections are frequent. Genotype I appears to be the predominant genotype in the studied population. Combined molecular and serological testing may improve the detection and epidemiological characterization of E. cuniculi infections in rabbits.